Kesalahan Berbahasa Tataran Sintaksis pada Tugas Keterampilan Menyimak Pemelajar BIPA Program KNB di Universitas Negeri Surabaya - Cahyo, Anggoro Abiyyu Ristio; Sodiq, Syamsul; Inayatillah, Fafi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Language is a communication tool that consists of spoken and written language. Writing assignments must be in accordance with linguistic rules, but errors often occur in its application. This study aims to describe the types of language errors in the syntax level. The approach of this research is qualitative. The method used in this research is descriptive. The data source used in this research is the assignment of BIPA learners of KNB program in Writing Skills course at Surabaya State University. The data collection techniques used in this research are listening and note-taking techniques. The data analysis technique in this research is based on six language error procedures, namely data collection, data identification, data classification, determination of frequency and distribution of errors, identification of error areas, and error correction. The result of this research shows that there are phrase and sentence construction errors in the assignments of BIPA learners of KNB program at Surabaya State University.